ENERGY LOSS COMPARISON OF TRANSFORMERS WITH AMORPHOUS AND CRGO CORES - Hudson, Ferro
The amorphous core transformer represents a new technological advancement aimed at improving transformer efficiency, particularly in reducing energy losses. As Indonesia's energy demand continues to grow rapidly, there is a critical need to implement more efficient technologies to reduce production costs and minimize environmental impact. This study evaluates the performance of amorphous core transformers in comparison with traditional Cold Rolled Grain Oriented (CRGO) transformers, focusing on energy losses and their environmental effects. The evaluation was conducted through direct measurements of transformer losses, supported by references from existing literature, and provides the potential annual loss reduction and carbon emission reduction at PT PLN (Persero). The analysis revealed a significant disparity in no-load losses between amorphous and CRGO transformers, with the difference becoming more pronounced as transformer size increases. Amorphous core transformers consistently demonstrated lower no-load losses, indicating superior efficiency, especially for larger units. Furthermore, the potential for reducing load losses was assessed, showing that amorphous transformers can lead to substantial savings. This research has found that these transformers, based on the quantity used by PT PLN (Persero), have the capability to reduce production costs by up to IDR 54.101.000.000 annually, while also contributing to a reduction in carbon emissions by 29.996 tons of CO2 per MWh. This research highlights the potential of amorphous core transformers as a key technology in addressing Indonesia’s growing energy needs. By significantly reducing both operational costs and environmental impact, amorphous transformers offer a promising solution for enhancing the sustainability and efficiency of the country’s energy infrastructure.